Evaluación de los conocimientos de las madres sobre las enfermedades prevalentes de la infancia para mantener un nivel adecuado de salud, en el SCS de la Cooperativa 20 de Febrero, provincia de Los Ríos, año 2014 - Uzho Rizzo, Verónica Marisol (2015)
This research was conducted to know the knowledge of mothers on prevalent childhood diseases (IMCI) to maintain an adequate level of health, in the SCS Cooperative February 20, Rivers Province 2014, to thereby develop a strategy applied education and skills to further identify each one of the mothers of children under five. The research used was not experimental, as an instrument of data collection survey was used, with its own questionnaire, the same as I consist with items with different response options. The instrument was validated through a pilot test applied in health Subcentro Cooperative February 20, Rivers Province during 2014. The study conducted with 90 mothers of children under five years significantly showed that 45% believe they have always received lectures on prevalent childhood diseases, while 55% say they rarely have received lectures on this topic. The results of this study demonstrate that 100% of mothers of children under five years if they express interest in everything that relates to prevalent childhood diseases in which they participated and gained knowledge, facilitating exchange of experiences. Its purpose is to reduce mortality, morbidity and disability in children under five, and promote better growth and development.